2014
DOI: 10.4172/2327-5146.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in Patients with Diabetes Mellitus: Prevalence and Progression

Abstract: Aim: Anemia is found to contribute to the development and progression of micro and macro-vascular complications of diabetes. This study aimed to determine the prevalence of anemia in patients with diabetes and the occurrence of micro and macro vascular complications in them.Method: This was a retrospective study of 227 Saudi patients with diabetes regularly followed up as outpatients for one year. Patient's demographic profile, history of stroke, ischemic heart disease (IHD), and concomitant hypertension (HT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
1
3
2
Order By: Relevance
“…However, it was higher than other reports from various regions of the world, ranging from7.7% in the USA to 22% in China [7, 11, 12, 14, 19]. On the other hand, the magnitude of anemia in this study was lower compared to the findings of other studies conducted in different corners of the world, varying between 41.1% in Sub-Saharan Africa (Cameroon) and 67% in India [6, 10, 15, 16, 20]. The variations might be due to differences in socio-demographic and economic status, access to health care services, feeding habits, lifestyle, scale of study, measurements, and altitude.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, it was higher than other reports from various regions of the world, ranging from7.7% in the USA to 22% in China [7, 11, 12, 14, 19]. On the other hand, the magnitude of anemia in this study was lower compared to the findings of other studies conducted in different corners of the world, varying between 41.1% in Sub-Saharan Africa (Cameroon) and 67% in India [6, 10, 15, 16, 20]. The variations might be due to differences in socio-demographic and economic status, access to health care services, feeding habits, lifestyle, scale of study, measurements, and altitude.…”
Section: Discussioncontrasting
confidence: 81%
“…Serious complications of early onset anemia in diabetic patients include severe symptomatic neuropathy leading to efferent sympathetic denervation of the kidney and possible damage to the renal interstitial and inability to produce appropriate erythropoietin, systemic inflammation and inhibition of erythropoietin release [28, 29]. Anemia is found to contribute to the development and progression of micro and macro-vascular complications of diabetes, which has a negative impact on the quality of life and an additional burden on the health of the patients [7, 15, 30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis estimated a prevalence of 35% for anemia among patients with T2DM in Africa [18]. Compared to ours, other studies conducted in Kuwait ( 6), Malaysia [19], Brazil [20], Greece (among patients with DKD stages 2-4) [21,22], Saudi [23], England [24], and Pakistan [25], revealed a higher prevalence of anemia among patients with T2DM, which were 29.7% , 31.7%, 34.2% , 34.7%, 47.8%, 55.5%, 59%, and 63%, respectively ; however, a study from India [10] and a community-based cohort from Australia [8] showed a lower prevalence of 12.13% and 11.5%, respectively. These differences may be due to the quality of healthcare services, such as accessibility of patients to visit a specialist and laboratory testing besides.…”
Section: Discussioncontrasting
confidence: 48%
“…This finding is in accordance with the recent meta-analysis that reported the prevalence of anemia at 27% (12). However, the prevalence of anemia in our study is lower when compared with the findings of the study conducted in Sub-Saharan Africa (41.1%), Iran (33.4%), Malaysia (31.7%), Saudi Arabia (47.8%), and Pakistan (59%) (13,(25)(26)(27)(28). These results may highlight the variability of healthcare quality in developing countries.…”
Section: Discussionsupporting
confidence: 91%